Gender Equality in Academia from Knowledge to Change - Holte, Øystein Gullvåg (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
What is the state of gender equality in science and technology? Gender Equality in Academia - from Knowledge to Change presents the results of a comprehensive research project and program of initiatives at the University of Oslo's Faculty of Mathematics and Natural Sciences. Researchers have examined gender equality within the department, looking at reasons for imbalance, and at what occurs when measures to promote equality are implemented. The book opens with an in-depth study of careers, gender issues and gender balance within academia. The study, based on questionnaires, interviews and follow-up evaluation, provides a new and updated understanding of the daily lives of academics in Norway. Among the topics covered are perceptions of equality and gender balance, effects of male dominance, sexual harassment, gender with respect to publishing, and the relationship between gender and diversity. In addition to presenting new empirical data, the book is also an innovative contribution to theoretical development within gender equality research. In the second part of the book, the authors present three working models that elucidate current mechanisms recreating gender imbalance, and challenges for gender equality. The book's final part consists of analyses of measures taken to increase gender equality within the department and their effects, and what an organization can do to increase gender equality. The range of topics in this book make it relevant for everyone concerned with gender equality in research and higher education. Researchers, administrators, students, other practitioners, and politicians will all find this book of interest.